FLOOD RISK PATTERN RECOGNITION IN RAJANG RIVER BASIN, SARAWAK - NurIzzati Salleh; Ahmad ShakirMohd Saudi; NurZahidah Shafii; Djoko Roespinoedji (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Flood is one of the natural disaster events in Malaysia. The flood occurred due to overflow of the excessive water level in the river system which causing land sinking and major disruption towards the human and environment. The objective of this study is to evaluate the flood risk index in the Rajang River Basin. A set of the database from 1989-2019 were gathered from Department of Irrigation and Drainage (DID) and were analysed using Principal Component Analysis(PCA),StatisticalProcessControl(SPC)andFloodRiskIndex(FRI).Theapplication of statistical process control (SPC) had revealed the most the significant factors of flood occurrencebyusingprincipalcomponentanalysis(PCA)inRajangRiverBasinthroughwater levelpredictionatthestudyareabydeterminingthecontrollimitvalue.Waterlevelprediction helps to develop the flood risk index (FRI) which can show the current and future prediction in the Rajang River Basin, also helps the local authorities for flood control, and reduce the impact of flood in Sarawak. Based on the findings, the most significant factors identified for the occurrence of flood in the Rajang River Basin are water level, rainfall, and evaporation, which eventually lead to high increases in water level. In conclusion, uncontrolled deforestation due to rapid development in the upriver areas also have worsened the flood occurrence situation evenworse.